2018
DOI: 10.1097/aln.0000000000001979
|View full text |Cite
|
Sign up to set email alerts
|

Using Activity Trackers to Quantify Postpartum Ambulation

Abstract: Background Early postoperative ambulation is associated with enhanced functional recovery, particularly in the postpartum population, but ambulation questionnaires are limited by recall bias. This observational study aims to objectively quantify ambulation after neuraxial anesthesia and analgesia for cesarean delivery and vaginal delivery, respectively, by using activity tracker technology. The hypothesis was that vaginal delivery is associated with greater ambulation during the first 24 h po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The lower incidence of motor blockade observed in postpartum women using PIEB in this study may be associated with the benefits of early ambulation, as recommended by the Enhanced Recovery After Surgery (ERAS) guidelines [ 22 , 23 ]. Early ambulation is an important clinical indicator for maternal health and neonatal care as it indicates better postoperative recovery and ensures maintenance of maternal independence during the postpartum period [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lower incidence of motor blockade observed in postpartum women using PIEB in this study may be associated with the benefits of early ambulation, as recommended by the Enhanced Recovery After Surgery (ERAS) guidelines [ 22 , 23 ]. Early ambulation is an important clinical indicator for maternal health and neonatal care as it indicates better postoperative recovery and ensures maintenance of maternal independence during the postpartum period [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Her postpartum course was uncomplicated, and it is unknown if her extremely high level of physical activity was intentional. While previous studies have shown a good accuracy of Fitbit TM devices for step counts [ 11 , 12 , 32 , 33 ], one systematic review suggested that Fitbit TM devices can overestimate steps in free-living settings [ 13 ]. To decrease the risk of overestimation, we conducted a sensitivity analysis to exclude the step count data of this participant.…”
Section: Discussionmentioning
confidence: 99%
“…Ma et al previously demonstrated that step count during the first 24 hours after vaginal delivery with epidural analgesia was 1,205 ± 422 (mean ± SD) [ 12 ]. Assuming that a 20% difference in the 24-hour step count would be clinically meaningful [ 12 ], we performed a two-sided test of superiority of the 24-hour step count and determined that a sample of at least 31 participants per group will provide 80% power at a 5% significance level (type I error estimate).…”
Section: Methodsmentioning
confidence: 99%
“…Yet, a limited number of studies have assessed postpartum mobility with their use. In a study by Ma and colleagues, patient mobility during the first 24 h following delivery was assessed with activity trackers [10].…”
Section: Discussionmentioning
confidence: 99%
“…Immobility, which characterizes the immediate postpartum period, has been previously demonstrated to contribute to the pathogenesis of VTE [7]. Previous studies have addressed post-partum immobilization, and linked it to an increased risk for VTE [8], yet only a limited number have objectively quantified mobility with digital step counters [9][10][11]. Moreover, none of the previous studies have assessed the efficacy of an intervention for reducing post-partum immobilization.…”
Section: Introductionmentioning
confidence: 99%